Developing an integrated service training model for local restaurant waiters: Evidence from Manado, Indonesia - Benny Irwan Towoliu (Jurnal Pendidikan Vokasi, 2025)
Tourism development in Manado has stimulated rapid restaurant growth, yet improvements in human resources have not kept pace, particularly among local waiters whose service competence remains limited. Existing training programs are often generic, insufficiently contextualized, and unable to accommodate participants’ different educational and work backgrounds. This study aims to develop an integrated service training model specifically designed for waiters in local restaurants. A mixed-method approach was employed combining questionnaires, observations, and interviews with customers, restaurant owners, and waiters. Survey data were analyzed descriptively to identify gaps between service expectations and performance, while qualitative data were examined thematically to explore service problems and training needs. The findings indicate a clear discrepancy between customers’ high expectations and the actual service performance of local waiters, particularly in communication, product knowledge, service etiquette, and problem-handling. The proposed integrated model groups participants based on prior education and experience, and applies differentiated training methods: basic training (video presentation/vestibule), intermediate training (role-play), and advanced training (case studies and managerial problem-solving). Competencies are assessed at each stage and recognized through certification at different levels. The model proves effective in aligning training content with participant needs, preventing training fatigue, and generating clearer competency outcomes. This study contributes to vocational education and tourism by demonstrating how workplace-based training can be structured, competency-oriented, and certification-ready, while supporting local workforce readiness and service quality improvement.